1966
DOI: 10.2307/2406149
|View full text |Cite
|
Sign up to set email alerts
|

Selection for Increased Fertility of Female Quail When Mated to Male Chickens

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. Society for the Study of Evolution is collaborating with JSTOR to digitize, preserve and extend access to Evolution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

1970
1970
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 5 publications
1
3
0
Order By: Relevance
“…Furthermore, the survival rate of hybrid embryos decreased gradually thereafter: 21% embryos survived at 5 days, 15% at 10 days, and 14% at 12 days. There was large variation in fertilization and survival rates between individual female quail, which concurs with previous studies (Haley et al, 1966;Takashima and Mizuma, 1981). Therefore, fertilization and survival rates are likely to fluctuate across studies.…”
Section: The Inviable Phenotype Of Chicken × Quail Hybridssupporting
confidence: 92%
“…Furthermore, the survival rate of hybrid embryos decreased gradually thereafter: 21% embryos survived at 5 days, 15% at 10 days, and 14% at 12 days. There was large variation in fertilization and survival rates between individual female quail, which concurs with previous studies (Haley et al, 1966;Takashima and Mizuma, 1981). Therefore, fertilization and survival rates are likely to fluctuate across studies.…”
Section: The Inviable Phenotype Of Chicken × Quail Hybridssupporting
confidence: 92%
“…Preliminary evidence for the existence of such an immunological mechanism causing reduced inter-376 L. E. Haley and H. Abplanalp specific fertility was found in a selection experiment where quail [Coturnix coturnix japónica) hens were routinely tested for their ability to produce hybrids when inseminated with fowl {Gallus domesticus) semen (Haley, Abplanalp & Enya, 1966;Haley, 1967 Experimental inseminations in Groups I and II were begun when the quail hens were 22 weeks old, 7 weeks after the preliminary fertility tests were dis¬ continued. In Group III, the lapse in inseminations after preliminary tests lasted 13 weeks, until the hens were 28 weeks old.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies suggested a large difference in fertilization rate between female quail individuals 37 39 . Thus, we analyzed the fertilization, survival, and hatching rates for each quail individually.…”
Section: Resultsmentioning
confidence: 92%
“…The fertilization rate in the interspecific crosses is low, ranging from 5.4 to 25.3% 33 34 35 36 37 38 . The fertilization rate is largely different among breeds of chickens and quail strains used for hybridization 33 37 39 . In most fertilized eggs, embryonic development is arrested around the formation of the extraembryonic membrane and/or blood islands, and in a small fraction of the remaining fertilized eggs, hybrids are hatched 37 .…”
mentioning
confidence: 99%